Periodontitis and prevalence of elevated aminotransferases in the Hispanic Community Health Study/Study of Latinos. Issue 8 (17th August 2018) - Akinkugbe, Aderonke A.; Barritt, A. Sidney; Cai, Jianwen; Offenbacher, Steven; Thyagarajan, Bharat; Khambaty, Tasneem; Singer, Richard; Kallwitz, Eric; Heiss, Gerardo; Slade, Gary D.
Abstract: Background: Non‐alcoholic fatty liver disease (NAFLD) prevalence is greater among Hispanics/Latinos than other racial/ethnic groups and prevalence is further reported to vary among Hispanic/Latino background groups. Experimental animal and human studies demonstrate associations between periodontitis and NAFLD, not yet reported among Hispanics/Latinos. This study examined periodontitis as a novel risk factor that may contribute to the burden of NAFLD among Hispanics/Latinos. Methods: Data came from 11, 914 participants of the Hispanic Community Health Study/Study of Latinos. Periodontitis was defined as the extent (none,  < 30%, ≥30%) of periodontal sites with clinical attachment level (CAL) of ≥3 mm or probing pocket depth (PD) of ≥4 mm. Elevated serum transaminases indicative of suspected NAFLD were defined as having alanine aminotransferase levels (ALT) > 40 IU/L or aspartate aminotransferase (AST) > 37 IU/L for men and ALT > 31 IU/L or AST > 31 IU/L for women. Survey‐logistic regression models estimated prevalence odds ratios (POR) and 95% confidence intervals (CI) for the association between periodontitis and suspected NAFLD. Results: The overall age‐standardized percentage of study participants with < 30% of sites with CAL ≥3 mm or PD ≥4 mm was 53.5% and 58.6%, respectively, while participants with ≥30% sites with CAL ≥3 mm or PD ≥4 mm comprised 16% and 5.72%, respectively. The overall age‐standardized prevalence (95% CI) of suspected NAFLD was 18.1% (17.1‐19.0). For the entire cohort, we observed a dose‐response (i.e. graded) association between PD ≥4 mm and the prevalence odds of suspected NAFLD, whereby participants with < 30% affected had a crude POR = 1.19 (95% CI: 1.03, 1.38) while participants with ≥30% affected had a crude POR = 1.39 (95% CI: 1.02, 1.90). These crude estimates were attenuated toward the null and rendered non‐significant upon covariate adjustment. No differences were found by Hispanic/Latino background group. Conclusion: Previously reported associations between periodontitis and NAFLD were marginal to null in this study of a diverse group of Hispanics/Latinos.